2007
DOI: 10.1007/s11064-007-9336-7
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β-Peptide Reduces the Expression Level of Mitochondrial Cytochrome Oxidase Subunits

Abstract: Mitochondrial dysfunction is an important cause of neurological disorder including Alzheimer's disease (AD). Mitochondria play a key role in the generation of reactive oxygen species (ROS), resulting in oxidative damage to neuronal cell and cellular compartments in the AD brain. Cytotoxicity induced by amyloid-beta (Abeta), a protein fragment of 25-35 amino acids in amyloid plaques has been shown to have neuro-toxic properties. They seem to involve mitochondrial dysfunction, but the underlying mechanisms are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…We have shown that excessive APP and Ab contributes to the mitochondrial abnormalities [160]. This concept of AbPP/Ab mitochondrialtoxicity is now supported by studies in other systems, especially as putatively related to AD and Parkinson brain [156,161,162]. a-synuclein accumulated in s-IBM muscle fibers may, in oligomeric and misfolded forms, also contribute to mitochondrial toxicity [161].…”
Section: Mitochondrial Abnormalitiesmentioning
confidence: 69%
“…We have shown that excessive APP and Ab contributes to the mitochondrial abnormalities [160]. This concept of AbPP/Ab mitochondrialtoxicity is now supported by studies in other systems, especially as putatively related to AD and Parkinson brain [156,161,162]. a-synuclein accumulated in s-IBM muscle fibers may, in oligomeric and misfolded forms, also contribute to mitochondrial toxicity [161].…”
Section: Mitochondrial Abnormalitiesmentioning
confidence: 69%
“…Although the specific effects of these peptides on mitochondria are still under investigation, A␤ has been demonstrated to accumulate into this organelle and destabilize its membrane properties (35,36). Deleterious effects of A␤ on the mitochondrial function include reduced cytochrome c oxidase activity (35,37) caused by inhibition of its gene expression (37), decreased respiration and ATP synthesis, and cytochrome c release (35,38).…”
Section: Discussionmentioning
confidence: 99%
“…1). Supporters of the amyloid cascade hypothesis have used it to explain AD-related mitochondrial pathology because: 1) AβPP and Aβ accumulates in mitochondria from brains of transgenic mice and AD subjects [144][145][146][147]; 2) binding of Aβ to the mitochondrial proteins Aβ-binding alcohol dehydrogenase and cyclophilin D is associated with increased oxidative stress, cytochrome c release, reduced mitochondrial membrane potential, and neuronal cell death [146,148]; 3) features of reduced Krebs cycle and ETC enzymatic activity, impaired state 3 and state 4 respiration, and in vivo elevation of oxidative stress demonstrated in AD and transgenic mouse brains were associated with Aβ [126,[149][150][151][152][153][154][155]; and 4) the direct reduction of cytochrome oxidase expression and activity by Aβ 42 and Aβ 25−35 (a toxic Aβ fragment) supported this hypothesis [48,156,157]. Though evidence for Aβ-induced pathology is plentiful, PET-scan measured reductions in brain glucose metabolism in MCI and AD individuals [158][159][160][161] warrant a further look at the role mitochondrial bioenergetics play.…”
Section: Mitochondrial Cascade Hypothesismentioning
confidence: 92%